Transforming Raudhatul Athfal Educator Training through Applicative Approaches and Data Based Accurate Training Needs Analysis - Wawan Hermawan (JURNAL ILMIAH GEMA PERENCANA, 2026)
This policy aims to address the low pedagogical competence of Raudhatul Athfal educators in implementing modern curricula, which has been hindering the quality of the early childhood education foundation. The main identified problems include the lack of applicative training and inaccurate training needs analysis, resulting in a gap between theory and field practice. The policy methodology employed in this paper begins with a situational analysis using the Urgency, Seriousness, and Growth method to objectively determine problem-solving priorities. Furthermore, the root causes are analyzed through a fishbone diagram to map various inhibiting factors, ranging from digital literacy aspects to institutional management. The evaluation of five policy alternatives was conducted by applying William N. Dunn’s criteria, which include effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness to identify the most feasible solution. Based on the assessment results, the recommended policy is the enactment of the Decree of the Minister of Religious Affairs regarding the Revitalization of Teacher Working Groups and the Raudhatul Athfal Teachers Association as Clinical Mentoring Institutions. This strategic step prioritizes the transformation of learning communities from mere administrative forums into centers for continuous and structured pedagogical mentoring at the grassroots level. Through this peer-mentoring mechanism, a tangible change in teaching behavior is expected, where teachers are able to perform authentic assessments and manage child-centered learning according to the independent curriculum mandate, in order to prevent the degradation of human resource quality in the future.